Fossil neoliberalism and its limits: Governing coal in South India. (December 2022) - Kumar, Mukul
Over the last three decades of neoliberalization, India's fossil fuel infrastructures have been transformed into an archipelago of coal-fired power plants and industrial ports in coastal zones. Drawing upon the case of coal infrastructures sited on the coast of south India, this article tracks processes of what I call "fossil neoliberalism": the ways in which neoliberal modes of governance have transformed the state into an agent of market-based fossil fuel extraction. The article calls for attention to how particular technologies of governance—from disinvestment and initial public offerings to corporatized landlord ports—have reconfigured and respatialized, rather than reduced, the role of the state in processes of fossil fuel extraction. The article also analyzes how fossil neoliberalism, as an ensemble of market-based technologies of governance, is enabled by coastal zone illegalities and limited by political mobilizations.